Extraordinary Thermoelectric Performance Realized in n‐Type PbTe through Multiphase Nanostructure Engineering. Issue 39 (21st August 2017) - Zhang, Jian; Wu, Di; He, Dongsheng; Feng, Dan; Yin, Meijie; Qin, Xiaoying; He, Jiaqing
Abstract: Lead telluride has long been realized as an ideal p‐type thermoelectric material at an intermediate temperature range; however, its commercial applications are largely restricted by its n‐type counterpart that exhibits relatively inferior thermoelectric performance. This major limitation is largely solved here, where it is reported that a record‐high ZT value of ≈1.83 can be achieved at 773 K in n‐type PbTe‐4%InSb composites. This significant enhancement in thermoelectric performance is attributed to the incorporation of InSb into the PbTe matrix resulting in multiphase nanostructures that can simultaneously modulate the electrical and thermal transport. On one hand, the multiphase energy barriers between nanophases and matrix can boost the power factor in the entire temperature range via significant enhancement of the Seebeck coefficient and moderately reducing the carrier mobility. On the other hand, the strengthened interface scattering at the intensive phase boundaries yields an extremely low lattice thermal conductivity. This strategy of constructing multiphase nanostructures can also be highly applicable in enhancing the performance of other state‐of‐the‐art thermoelectric systems. Abstract : A new strategy of constructing multiphase nanostructures can enhance the thermoelectric power factor and reduce the lattice thermal conductivity simultaneously. Through this strategy, it is reported that a record‐high ZT value of ≈1.83 can be achieved at 773 K in n‐type PbTe‐4%InSb composites. Furthermore, the mechanisms introducing multiphase nanostructures are also highly applicable in other thermoelectric systems.